Media pembelajaran IPS pasca pandemi Covid-19 - Yayan Sudrajat (Jurnal Ilmiah Wahana Pendidikan, 2022)
This article aims to determine the use of learning media in the form of online learning using applications available on devices used by teachers in carrying out classroom learning. This study uses a survey method with samples taken from 3 provinces in Indonesia. Applications that are often used in social studies learning are: Google Meet, Google Classroom, G-Form, Meeting Zoom